Communication of innovations : a journey with Ev Rogers - Singhal, Arvind, 1962-; Dearing, James W. (New Delhi : SAGE Publications, 2006)
Everett M. Rogers, 1931-2004, communications scholar and pioneer of diffusion of innovations theory; contributed articles.
1. Communication of innovations : a journey with Ev Rogers / James W. Dearing and Arvind Singhal -- 2. Revisiting diffusion theory / James W. Dearing and Gary Meyer -- 3. Communication network analysis and the diffusion of innovations / Thomas W. Valente -- 4. Innovation as a knowledge generation and transfer process / Dorothy A. Leonard -- 5. On integrating social cognitive and social diffusion theories / Albert Bandura -- 6. Social marketing and the broadening of marketing movement / Philip Kotler -- 7. Communication and social change in developing countries / Srinivas Melkote -- 8. Implementing strategic extension campaigns : applying best practices and lessons learned from Ev Rogers / Ronny Adhikarya.
Includes bibliographical references and indexes.
Keywords: Rogers, Everett M; Rogers, Everett M; Communication of technical information